Stakende bouwvakkers wachten op hun stakingsuitkering voor gebouw "De Arend" in de Planciusstraat - Kruger, Dolf,
Stakende bouwvakkers wachten op hun stakingsuitkering voor gebouw "De Arend" in de Planciusstraat.